The Caribbean Leadership project : celebration the Caribbean Leadership Project 2011-2018 (2018)
Celebrates the Caribbean Leadership Project (CLP), a partnership between the Government of Canada through the Canada School of Public Service, Caribbean Centre for Development Administration (CARICAD) and the Governments of CARICOM to help boost the reservoir of leadership skills among senior public sector personnel in the Region.
Keywords: DEVELOPMENT TRAINING